Ionic strength of the liquid phase of different sludge streams in a wastewater treatment plant. (15th February 2022) - Prot, T.; Korving, L.; Van Loosdrecht, M. C. M.
Abstract: In a wastewater treatment plant (WWTP), several sludge streams exist and the composition of their liquid phase varies with time and place. For evaluating the potential for formation of precipitates and equilibria for weak acids/bases, the ionic strength and chemical composition need to be known. This information is often not available in literature, and even neglected in chemical model-based research. Based on a literature review, we proposed three ranges of concentration (low, typical and high) for the major constituents of the liquid phase of the different streams in a WWTP. The study also discusses the reasons for the concentration evolution, and the exceptional cases, to allow readers to consider the right range depending on their situation. The ionic strength of the different streams and the contribution of its constituents were calculated based on the ionic composition. The major contributors to the ionic strength for the wastewater-based streams (influent, effluent and mixed sludge) were Na +, Cl −, Mg 2+ and Ca 2+, representing 50–70% of the ionic strength. For digestate, and accounted for 65–75% of the ionic strength. Even though the ionic strength is recognized to impact several important wastewater treatment processes, its utilization in literature is not always adequate, which is discussed in this study. HIGHLIGHTS: The ionic strength for wastewater-based streams ranges from 0.003 to 0.1 M. Na +, Cl −, Mg 2+ and Ca 2+ make 50–70% of the wastewater-based streams' ionic strength. The ionic strength for digestates ranges from 0.02 to 0.17 M. NH 4+ and account for 65–75% of the ionic strength of digestates. Ionic strength is rarely determined and often misused in literature. Graphical Abstract